An Investigation into Providing Additional Parking to Solve Stellenbosch’s Parking and Congestion - Hughes, B.C.M.; Visagie, C.B. (The South African Journal of Industrial Engineering, 2025)
Stellenbosch, a small university town in South Africa, experiences severe parking shortages and traffic congestion. In response to the increasing parking demand, the local municipality proposed the development of a new multi-level parking facility next to the Eikestad shopping centre, located in the central business district of Stellenbosch. However, for this proposed solution to be viable, it must satisfy the needs of all affected stakeholders. To integrate stakeholder input more easily into the planning process, a product development evaluation tool, called the “house of quality”, was used. This tool enables the key stakeholder requirements, relevant design attributes, and potential site locations for the proposed multi-level parking facility to be identified. The house of quality’s results demonstrated its effectiveness in generating valuable insights for informed decision-making. Nevertheless, to ensure that the proposed parking facility accurately reflects the needs of the affected stakeholders, further studies are necessary.